2004
DOI: 10.1017/s0024282904014112
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of lichen species richness in a disturbed ecosystem (Niepołomice Forest, S Poland)

Abstract: The spatial pattern of lichen species richness was analyzed in a forest ecosystem impacted for 50 years by industrial emissions from a steelworks. Geostatistical tools were used to characterize the spatial pattern of the number of lichen species and multiple regression analysis was used to identify factors influencing it. Spatial analysis showed high variation of lichen species richness on a local scale, caused by patchiness of natural habitat factors (species composition of trees, their age, shade, etc.). On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Other authors report different results from other and more geomorphologically homogeneous regions (e.g. Poland - Kapusta et al 2004), where one can assume considerable long-distance transport of pollutants. This is, on the contrary, very limited in Liguria.…”
Section: Axis 1 and Axis 2: Interactions Among Factorsmentioning
confidence: 85%
“…Other authors report different results from other and more geomorphologically homogeneous regions (e.g. Poland - Kapusta et al 2004), where one can assume considerable long-distance transport of pollutants. This is, on the contrary, very limited in Liguria.…”
Section: Axis 1 and Axis 2: Interactions Among Factorsmentioning
confidence: 85%
“…Niepolomice Forest - Turnau, 1988;Kapusta et al ., 2004;Chernobyl -Zhdanova et al ., 2004). Our work presents a survey of AM colonization in A5 hill using morphological and molecular methods.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies found in literature on ‘biological deserts’ resulting from industrial wastes and emissions, there are cases of investigations in which, besides human, plant and animal health, also the microbial communities had been considered (for example, the areas contaminated by metal smelters in Finland, Northern Sweden and Canada –Gunn et al ., 1995; Pennanen et al ., 1996; Palmborg et al ., 1998). However, to our knowledge, only few of them analysed the microbial component represented by mycorrhizal fungi (for example: Niepolomice Forest –Turnau, 1988; Kapusta et al ., 2004; Chernobyl –Zhdanova et al ., 2004). Our work presents a survey of AM colonization in A5 hill using morphological and molecular methods.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of plant uptake and accumulation of contaminants varies significantly among plant species and are mainly limited by their nonpolar and hydrophobic nature and strong association with soil organic fractions 7 . Moreover, there are several variables which include the initial soil PAH concentration, soil properties, contaminant properties and environmental factors that significantly influence the uptake, accumulation and metabolism of PAHs in plants 8 .…”
Section: Introductionmentioning
confidence: 99%